786 SYSTOLIC ANTERIOR MOVEMENT OF MITRAL VALVE: NOT ONLY HYPERTROPHIC CARDIOMYOPATHY, BUT ALSO CARDIAC AMYLOIDOSIS. (15th December 2022) - Accietto, Antonella; Giovannetti, Alessandro; Caponetti, Giuseppe Angelo; Saturi, Giulia; Sguazzotti, Maurizio; Ponziani, Alberto; Longhi, Simone; Gagliardi, Christian
Abstract: A 71 years-old man was diagnosed with lambda light chain multiple myeloma evolving from monoclonal gammopathy of unknown significance during hematological follow-up. Serum creatinine and blood urea were normal, but proteinuria was significant. A subsequent renal biopsy showed amyloid deposits in renal glomeruli. He had no comorbidities or previous cardiologic history. To provide a complete diagnostic work-up, an echocardiogram was performed, showing marked and asymmetric left ventricular hypertrophy (interventricular septum diastolic thickness IVSd 15 mm) with dynamic left ventricular outflow tract obstruction (LVOTO) due to an incomplete systolic anterior motion (SAM) of mitral valve. ECG showed sinus rhythm with 1 st degree atrio-ventricular block; notably, there was no electrocardiographic sign of left ventricular hypertrophy. Therefore, a Cardiac Magnetic Resonance (CMR) was performed, showing left ventricular hypertrophy (interventricular septum thickness 15 mm) with normal contractility. Mild left atrial enlargement and thickening of the interatrial septum were found, together with mild circumferential pericardial effusion. No perfusion defects were recorded, but late gadolinium enhancement (LGE) pattern was not assessable because of difficult myocardial signal nulling point. These findings were consistent with cardiac amyloidosis (CA). By the time, histological demonstration of amyloid was mandatory, so an endomyocardial biopsy was performed. Amyloid deposits were found to be in the myocardial interstitial space and into the myocardial vessel walls. Immunohistochemical staining revealed diffuse and high reactivity for lambda free light chains and moderate reactivity for kappa chains. No transthyretin was found in the specimens. Finally, a diagnosis of AL amyloidosis with cardiac and renal involvement associated with lambda light chain multiple myeloma was made and chemotherapy with bortezomib, thalidomide and dexamethasone (VTD) was started. During the cardiologic follow-up, three syncope with prodromal symptoms have occurred. In all these circumstances, no arrhythmias were found at prolonged ECG Holter monitoring. Echocardiogram showed a progression of the dynamic outflow obstruction to 80 mmHg and increasing mitral regurgitation associated with complete systolic anterior motion of the valve. Given the echocardiographic features and the clinical events, we performed a genetic blood test which excluded sarcomeric genes mutations. Also, familial screening with ECG and echocardiogram was negative. A better management of pharmacological therapy, together with avoidance of hypovolemia and supportive treatment of anemia finally relieved patient's symptoms. Conclusions: we presented this case to underline that, although rare, cardiac amyloidosis can resemble other hypertrophic cardiomyopathies with left ventricular outflow tract obstruction due to SAM of the mitral valve and irregular septal hypertrophy, caused by amyloid deposits. Most of these cases are seen in the senile transthyretin type, but sometimes they are observed in AL patients. Nowadays, it is crucial to diagnose these patients correctly as early treatment is critical for survival in this population.